Does stereotype threat influence age-related differences on directed forgetting tasks? - Chien, Jessie Chih-Yuan; Eich, Teal S. (Frontiers in Psychology, 2024)
Objectives The Directed Forgetting paradigm has proven to be a powerful tool to explore motivated forgetting in the lab. Past work has shown that older adults are less able to intentionally suppress information from memory relative to younger adults, which is often attributed to deficits in inhibitory abilities. Instructions in traditional Directed Forgetting tasks contain terms that may elicit stereotype threat in older adults, which may negatively impact memory. Here, we tested whether the instructions in a Directed Forgetting task affected older adults’ ability to appropriately control the contents of memory. Methods In two experiments that differed in the number of words presented (30 vs. 48 items), younger and older adults were randomized into one of four crossed Conditions of a Directed Forgetting task. At encoding, participants were either instructed to remember/ forget items, or to think about/not think about items. At test, they were either asked whether the memory probe was old or new, or whether they had seen it before (yes/no). Each experiment contained data from 100 younger (18– 40 years) and 98 older (60+ years) adults, with 25 participants per Condition. All participants were recruited from Prolific and tested online. Results In neither Experiment 1 nor Experiment 2 did we find evidence of a stereotype threat effect, or age-related effects of directed forgetting. We did find that performance for to-be-forgotten items was worse in conditions with encoding instructions that contained words that might trigger stereotype threat relative to conditions that did not contain such words: when explicitly told to forget items, both older and younger adults forgot more items than did participants who were cued to not think about the words and put them out of mind. However, we found no such difference across the two different remember instructions: regardless of whether participants were told to remember or to think about items, recognition memory for to be retained items was high. The pattern of results across the two experiments was similar, except, not surprisingly, participants performed worse in Experiment 2 than Experiment 1. Interestingly, we found that higher accuracy for to be remembered items was associated with a more positive outlook of one’s own memory relative to others. Discussion These results suggest that directed forgetting may not always be impaired in older adults.